Reference Echocardiographic Measurements in Very Low Birth Weight Preterm Infants - Calado, C.; Collins, C.; Drew, S.; Holberton, J. (American Journal of Perinatology, 2019)
Background Echocardiography is an important technique in neonatal care. The heart of a premature baby is known to be different from that of a term baby, and there is a paucity of literature regarding reference cardiac measurements for this population, especially for the very low birth weight (VLBW) infants.Objective We aimed to present reference values for echocardiography in VLBW preterm infants.Study Design This was a retrospective observational study taking place over an 11-year period. We collected data from the reports of echocardiographic examinations performed in a population of preterm infants born with gestational age ≤ 32 weeks and birth weight (BW) ≤ 1,500 g in the first week of life.Results Our study population included 1,244 preterm infants. We found BW to be an adequate and practical variable to use in relation to the cardiac measurements. We propose reference values for seven cardiac measurements presented in tables for each 100 g weight subgroup.Conclusion Our study, to the best of our knowledge, has the largest sample of VLBW preterm infants and provides easy-to-use information on cardiac measurements by echocardiography for both pediatric cardiologists and neonatologists.
Keywords: echocardiography; premature infant; very low birth weight infant